Effect of post bonding annealing on the reliability of Al based wire bondings in IGBTs. (November 2022) - Karanja, L.; Pichon, P.; Brandelero, J.; Legros, M.
Abstract: The reliability of Aluminium wire bonds in IGBTs is reported to be positively affected by a high temperature ultrasonic bonding or a post annealing treatment after wire bonding. This study focusses on the effect of the later and aims to explain the increase in lifetime recorded after power cycling tests on treated vs untreated modules. The reliability enhancement is linked to the microstructure modification of the Al wire/metallization interface as a result of the heat treatment. Using scanning and transmission electron microscopy, the microstructure evolution of heat-treated modules after power cycling is analyzed. The damage mechanisms of the heat treated, and non-treated Al top interconnects are compared. It is observed that the heat treatment improves the bonding interface thus slowing down the degradation of the wire bonds.